Sistem Informasi Geografis Wisata Pesisir Selatan - Surya Adi Nugraha; Sularno (Journal Of Informatics And Busisnes, 2024)
The utilization of Geographic Information Systems (GIS) has become crucial in the development of the tourism industry. This article presents a literature review on the application of GIS in the context of tourism. The review explores various GIS applications in destination management, tourism marketing, natural and cultural resource management, as well as tourism infrastructure development. The article also discusses the challenges and opportunities faced in adopting GIS in the tourism industry, including privacy issues, data integration, and sustainability. This research aims to provide a comprehensive understanding of the role and impact of GIS utilization in tourism development and to present future research directions in this field. By offering deep insights into the integration of GIS in the tourism industry, this article aims to provide guidance for practitioners, academics, and policymakers in harnessing the full potential of this technology to enhance the sustainability and competitiveness of the tourism sector globally.